Efectos de la aplicación de bioestimulantes orgánicos en la plantación de banano de la granja santa inés - Santos Suarez, Wilmer Bolivar (Machala : Universidad Técnica de Machala, 2021)
Of the agricultural products exported by Ecuador, bananas move around 9 million US dollars per year, exceeding 100 tons exported, for this reason and given the level of importance has been proposed as an objective to evaluate the effect of organic fertilization in the banana plant of the Santa Ines farm of the Faculty of Agricultural Sciences belonging to the Technical University of Machala, in the province of El Oro; an experimental design was used to determine the behavior of the treatments by the stimulus caused in them, it was necessary to observe the vegetative development of the banana plant using nutritional amendments and DAP to obtain the necessary information to determine the development and support the use of this technology; the approach of the research was descriptive and exploratory; the factors of the research were evaluated every 15, 16 and 17 days, these were: Pseudostem thickness, total leaves at parturition and plant height; after obtaining the information, it was tabulated in an Excel database for its respective interpretation; according to the results obtained, the ANOVA analysis of one factor, determined that there was significance between treatments because their values are less than (p= 0. 05) with respect to the plant height variable among the different treatments, according to the statistical analysis, in the Duncan test four statistically different homogeneous subsets were obtained, where we observed that the T1 treatment obtained a pseudostem thickness (86, 67 cm), in contrast to treatments T2 (83.50 cm), T3 (80.80 cm) and the control treatment (68.70 cm) that presented a smaller thickness with a difference of 17.97 cm, that is, that in controlled doses Kelpak (1.5Lt) does affect the growth of the circumference of the thickness of the pseudostem; to determine if there are statistically significant differences in the plant height variable, a one-factor ANOVA was carried out, the results obtained indicate that there was no significance because the values are greater than (p=0. 05), however, Duncan's homogeneity test did indicate a significant difference between treatments (p= 0. 05), being the T1 that reached a greater height at calving with (1.74 m), while in the control treatment T3 reached a height at calving (1.61 m), where we observed a difference of (0.13 m); in the growth in banana plant height from the beginning of the research until the last data collection; as for the variable leaves, the ANOVA analysis of one factor, determines that if there was significance between treatments that their values are less than (p= 0. 05); it was concluded that there was a significant difference between the four treatments, and that the best nutritional amendment for the variables pseudostem thickness (cm), plant height at emergence (m) and average leaves at parturition was the product Kelpak, which is the most advisable to be applied to the banana crop.
De los productos agrícolas exportados por Ecuador, el banano mueve alrededor de 9 millones de dólares americanos al año, sobrepasando las 100 toneladas exportadas, por este motivo y dada el nivel de importancia se ha planteado como objetivo evaluar el efecto de la fertilización orgánica en la plantilla de banano de la granja Santa Inés de la Facultad de Ciencias Agropecuarias perteneciente a la Universidad Técnica de Machala, en la Provincia de El Oro; se hizo uso de un diseño experimental para determinar el comportamiento de los tratamientos por el estímulo causado en ellos, se necesitó observar el desarrollo vegetativo de la planta de banano utilizando Enmiendas Nutricionales y DAP para la obtención de la información necesaria para determinar el desarrollo y apoyar el uso de esta tecnología; el enfoque de la investigación fue de tipo descriptivo y exploratorio; los factores de la investigación fueron evaluados cada 15, 16 y 17 días, estos fueron: Grosor pseudotallo, total hojas a la parición y altura de planta; luego de obtener la información, esta fue tabulada en una base de datos en Excel para su respectiva interpretación; de acuerdo con los resultados obtenidos, el análisis ANOVA de un factor, determinó que si hubo significancia entre los tratamientos debido a que sus valores son menores a (p= 0.05) en lo que respecta a la variable de altura de planta entre los diferentes tratamientos, de acuerdo al análisis estadístico, en la prueba Duncan se obtuvo cuatro subconjuntos homogéneos estadísticamente distintos, donde observamos que el tratamiento T1 obtuvimos un grosor de pseudotallo (86,67 cm), a diferencia de los tratamientos T2 (83,50 cm), T3 (80,80 cm) y el tratamiento testigo (68,70 cm) que presentaron un menor grosor con una diferencia de 17,97 cm, es decir, que en dosis controladas Kelpak (1,5Lt) si incide en el crecimiento de la circunferencia del grosor del pseudotallo; para determinar si hay diferencias estadísticamente significativas en la variable altura de planta, se realizó un ANOVA de un factor, los resultados obtenidos indican que no hubo significancia porque los valores son mayores a (p=0.05), sin embargo, la prueba de homogeneidad de Duncan sí indicó diferencia significativa entre los tratamientos (p= 0.05), siendo el T1 que alcanzó una mayor altura a la parición con (1,74 mts), mientras que en el tratamiento control T3 alcanzó una altura a la parición (1,61 mts), donde observamos una diferencia de (0.13 mts); en el crecimiento en la altura de planta de banano desde el inicio de la investigación hasta la última toma de datos; en cuanto a la variable hojas, el análisis ANOVA de un factor, determina que si hubo significancia entre los tratamientos que sus valores son menores a (p= 0.05); se llegó a la conclusión que si existe diferencia significativa entre los cuatro tratamientos, y que la mejor enmienda nutricional quedó para las variables grosor pseudotallo (cm), altura de planta a la aparición (mts) y promedio de hojas a la parición fue el producto Kelpak, es la más recomendable para ser aplicada al cultivo de banano.
Keywords: BANANO; EXPORTACIÓN; TRATAMIENTOS; ENMIENDA